Parenting experiences among fathers of prematurely-born children with cerebral palsy in South Korea - Jisun Park (Korean Academy of Child Health Nursing, 2021)
Purpose The symptoms and impairments caused by cerebral palsy usually require long-term treatment, resulting in a substantial burden on the family of affected children. This study explored the experiences of fathers with prematurely-born children with cerebral palsy, with a focus on how such experiences influenced their families. Methods A qualitative case study method was used. Nine subjects were recruited from April 2018 to June 2019 at one hospital, and each was interviewed three times by a neonatal nurse. Results Five core experiences of fathers were identified: regret for an insufficient initial response, confronting my child born as a premature baby, the position of being a dad who can't do anything, the process of treatment like a tunnel with no exit, and a father's getting meaning in life through children. These stories covered an individual's timeline and family interactions. Conclusion Our findings suggest that fathers of prematurely-born children tend to suppress their emotions; therefore, a novel intervention program to encourage fathers’ emotional expression and to support healthier interactions with their families is needed. Moreover, our findings could contribute basic information for the construction of a community-based support system to aid families, including prematurely-born children and other persons with impairments.